Perancangan dan Implementasi Video Company Profile sebagai Media Promosi di Faedah Shop - Hafsa Fitri AS. N (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
Faedah Shop is an online shop that sells unique gifts such as Mosaic Photos, Photo Boxes, Polaroid Frames and Stickers located in the city of Batam. This online shop focuses on unique gifts. However, until now, Faedah Shop does not have a promotional media that can provide information and introduce Faedah Shop to the general public and potential buyers of Faedah Shop. Therefore, we need a promotional media in the form of a video profile that can contain information and advantages of Faedah Shop. The methods used include interviewing the owner of the Faedah Shop, direct observation, and literature study. The results of this study will be implemented on Faedah Shop's social media, namely YouTube with the aim of the video profile being able to increase the interest of new prospective buyers to buy at Faedah Shop and be useful as a medium of information for the general public.